Practical Challenges in the Application of the Discounted Cash Flow (DCF) Model : in Terms of Business Valuation - Aho, Aleksanteri (My University, 2025)
This thesis investigates the practical challenges associated with the application of the Discounted Cash Flow (DCF) model in business valuation. While the DCF model is widely regarded as a theoretically robust tool for estimating intrinsic value, its real-world use is often complicated by subjectivity, uncertainty, and model sensitivity. The study aims to identify the most significant obstacles practitioners encounter when applying the DCF model and to evaluate how these challenges are addressed in professional settings. A qualitative research design was adopted, combining a review of academic literature with semi-structured interviews of two experienced finance professionals. The empirical findings confirm that the key difficulties lie in forecasting future cash flows, determining an appropriate discount rate, and estimating terminal value, each of which involves assumptions that can significantly influence the final valuation. Interviewees also emphasized the DCF model's reliance on heuristics and the limited availability of reliable data, particularly for non-public or early-stage companies. Despite these limitations, the DCF model remains a valuable tool when used alongside complementary valuation methods. Sensitivity and scenario analyses were highlighted as essential techniques for managing uncertainty and stress-testing assumptions. The study concludes that the greatest challenges in DCF valuation are not mathematical, but stem from the quality of inputs and the judgment required in their estimation. Consequently, effective application of the DCF model demands both technical competence and deep contextual understanding. These findings suggest that valuation profession- als should adopt a critical, context-sensitive approach to modeling, supported by a triangulation of valuation methods.

Tämä tutkielma tarkastelee diskontattuihin kassavirtoihin perustuvan mallin käytännön haasteita yrityksen arvonmäärityksessä. Vaikka DCF-malli nähdään yleisesti vankkana työkaluna todellisen arvon arviointiin, sen soveltaminen käytännössä on usein haastavaa mallin subjektiivisuuden, epävarmuuden ja oletuksien herkkyyden vuoksi. Tutkimuksen tavoitteena oli tunnistaa keskeisimmät käytännön haasteet, joita mallin käytössä esiintyy, sekä arvioida miten näitä haasteita käsitellään käytännön tasolla. Tutkimus toteutettiin laadullisena tutkimuksena, jossa yhdistettiin kirjallisuuskatsaus ja kaksi asiantuntijahaastattelua kokeneiden rahoitusalan ammattilaisten kanssa. Empiiriset havainnot vahvistivat, että suurimmat haasteet liittyvät kassavirtojen ennustamiseen, sopivan diskonttokoron määrittämiseen ja terminaaliarvon arviointiin. Nämä osa-alueet perustuvat oletuksiin, joilla on merkittävä vaikutus lopullisessa arvonmäärityksessä. Haastateltavat korostivat DCF-mallin riippuvuutta heuristiikoista sekä luotettavan datan rajallista saatavuutta, erityisesti listaamattomien tai varhaisessa kasvun vaiheessa olevien yrityksien kohdalla. Rajoitteistaan huolimatta DCF-malli säilyttää arvonsa työkaluna, kun sitä käytetään yhdessä täydentävien arvonmääritysmenetelmien kanssa. Herkkyys- ja skenaarioanalyysit nousivat keskeisiksi tekniikoiksi epävarmuuden hallinnassa ja oletusten kestävyyden testaamisessa. Tutkimuksen päätelmänä on, että DCF-mallin suurimmat haasteet eivät liity sen matemaattiseen rakenteeseen, vaan syötteiden ja oletuksien laatuun sekä niiden arviointiin liittyvään harkintaan. Mallin tehokas käyttö edellyttää sekä teknistä osaamista että syvällistä ymmärrystä liiketoiminnasta ja sen ajureista. Tulokset korostavat tarvetta kriittiselle ja tilannesidonnaiselle lähestymistavalle, jossa hyödynnetään useita arvonmääritysmenetelmiä rinnakkain lopputuloksen luotettavuuden parantamiseksi.
Keywords: discounted cash flow, business valuation, financial modeling, practical challenges, corporate finance